Inovasi Transformasi Digital Holistik di Jasa Raharja: Integrasi Sistem ERP, HRIS, dan Manajemen Data uuntuk Optimalisasi Layanan Publik - Purwantono, Rivan Achmad (Universitas Pahlawan Tuanku Tambusai, 2025)
Holistic digital reform transformation has become a strategic element in adaptive public services that focus on institutional efficiency. This study examines the application of integrative digital technology in Jasa Raharja through the implementation of the Enterprise Resource Planning (ERP) system, Human Resource Information System (HRIS), and data management based on blockchain technology and big data analytics. This digitalization strategy not only strengthens internal efficiency through automation of business processes and human resource management sources, but also supports cross-agency data synchronization in computing the national motor vehicle database, traffic accident data management, and insurance claim handling. The integration of the DASI-JR, IRSMS, and DORS systems has accelerated the process of disseminating information and claims, and significantly increased public tax compliance. With a systemic and data-based approach, this transformation contributes to the creation of more accountable, transparent, and participatory public governance. These findings indicate that ecosystem-based digitalization and multi-stakeholder collaboration are the main manifestations in realizing responsive and inclusive public services.